(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Political campaign discourse extends beyond literal meanings, relying on pragmatic strategies to shape public perception and influence voter behaviour. This study examines pragmatic modulation in the 2023 Nigerian presidential campaign speeches of Mr. Peter Obi, focusing on how linguistic strategies such as implicature, presupposition, metaphor, euphemism, and lexical pragmatics were employed to construct political narratives. The research adopts a qualitative discourse-analytic approach within the framework of Speech Act Theory and Relevance Theory in analyzing two purposively selected speeches: Obi’s pre-election address at Chatham House and his post-election speech following the Supreme Court judgment. The study identifies how Obi strategically adjusted his language to maximize contextual relevance, minimize cognitive effort, and enhance audience engagement. His pre-election speech emphasized reformist ideals, employing presuppositions and metaphors to frame governance challenges and solutions. His post-election speech, in contrast, modulated tone and implicature to manage political disappointment while reinforcing a continued political movement. By examining these shifts, the study highlights how pragmatic modulation is instrumental in shaping campaign rhetoric and post-election discourse. Findings contribute to political discourse and Nigerian political communication studies, offering insights into how candidates navigate sociopolitical realities, voter expectations, and electoral outcomes through language. The study underscores the need for further research into pragmatic strategies in African political discourse and their broader implications for democratic engagement. Keywords: , , ,